Location, Location, Location ‐ Strategic Positioning of 2, 1, 3‐Benzothiadiazole Units within Trigonal Quaterfluorene‐Truxene Star‐Shaped Structures. (17th January 2013) - Belton, Colin R.; Kanibolotsky, Alexander L.; Kirkpatrick, James; Orofino, Clara; Elmasly, Saadeldin E. T.; Stavrinou, Paul N.; Skabara, Peter J.; Bradley, Donal D. C.
Abstract: The fused, bicyclic molecule, 2, 1, 3‐Benzothiadiazole (BT), has become a key ingredient in the design of new organic semiconductors for light emission and energy harvesting applications. Here, the synthesis is reported of a series of trigonal, star‐shaped compounds comprising a truxene core and three quater‐dialkylfluorene arms into each of which a BT unit is inserted sequentially at each possible position (T4BT‐A to T4BT‐E). Analysis of the resulting electronic properties shows that as a consequence of conjugative coupling to the core and the resulting symmetry there are three distinct locations for the BT unit and the influence that these locations have on light emission and other spectroscopic characteristics is discussed. The systematic variation in photophysical properties for the different structural isomers helps to clarify the influence of BT unit addition to 9, 9‐dialkylfluorene chains. It also helps to establish a design template for the construction of donor‐acceptor conjugated materials with targeted properties. For T4BT‐E with a BT unit at the terminal position of each arm, the photoluminescence quantum efficiency is significantly reduced and no amplified spontaneous emission is observed under typical pumping conditions. Theoretical calculations assist in understanding the variation in behaviors among the T4BT‐X family of compounds, especially in relation to their photoluminescence decay times and the Raman scattering intensities of their dominant BT‐unit‐centred molecular vibrations. Abstract : 2, 1, 3‐benzothiadiazole (BT) units are systematically incorporated into star‐shaped trigonal molecules comprising a truxene core and three quaterfluorene arms. Five isomers are synthesized corresponding to the symmetric insertion of a single BT unit into each of the possible positions within the arms. Three BT locations are identified by comparison of absorption and photoluminescence (PL) spectra, supported by theoretical calculations. Additional experimental and theoretical characterizations reveal the influence of BT position on Raman, photoluminescence, and stimulated emission properties.